2016
DOI: 10.1016/j.lindif.2016.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Academic cheating and time perspective: Cheaters live in the present instead of the future

Abstract: Acknowledgements: We thank Ágnes Szokolszky for her helpful comments on the manuscript. According to Zimbardo and Boyd (1999), time perspective (TP) is an unconscious and individually determined attitude towards time. The conceptualization of psychological time includes three time zones: past, present and future. People differ in the manner they relate to time and this attitude is strongly related to a wide range of behavior. Several studies identified TP dimensions behind a broad variety of behaviors such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…The domain of FTP on school and professional career is particularly relevant for adolescents as they have to make many important decisions and plans regarding their future education and career (Paixão & Silva, 2001). Studies have found that adolescents with higher levels of FTP involve less in maladaptive behaviours such as "facebook addiction" and academic cheating and more in adaptive school behaviours (Gomes Carvalho & Novo, 2015;Orosz et al, 2016;Przepiorka & Blachnio, 2016). Also, FTP on school and professional career has been found to influence adolescents' motivation for school (Schuitema et al, 2014), Consequently, in this study we focus on adolescents' FTP on school and professional career.…”
Section: Future Time Perspectivementioning
confidence: 99%
“…The domain of FTP on school and professional career is particularly relevant for adolescents as they have to make many important decisions and plans regarding their future education and career (Paixão & Silva, 2001). Studies have found that adolescents with higher levels of FTP involve less in maladaptive behaviours such as "facebook addiction" and academic cheating and more in adaptive school behaviours (Gomes Carvalho & Novo, 2015;Orosz et al, 2016;Przepiorka & Blachnio, 2016). Also, FTP on school and professional career has been found to influence adolescents' motivation for school (Schuitema et al, 2014), Consequently, in this study we focus on adolescents' FTP on school and professional career.…”
Section: Future Time Perspectivementioning
confidence: 99%
“…Despite its prevalence, relatively little research has examined individual-level risk factors for academic dishonesty. To date, researchers have identified present time perspective (Orosz et al, 2016), low self-esteem (David, 2015), narcissism (Brunell, Staats, Barden, & Hupp, 2011), and blame externalization (Callender, Olson, Kerr, & Sameroff, 2010; Stanculescu, 2013) as risk factors for cheating behavior. Low self-control (Callender et al, 2010) and higher levels of sensation seeking (Deandrea, Carpenter, Shulman, & Levine, 2009; Etter, Cramer, & Finn, 2006) have also been associated with cheating and attitudes toward academic dishonesty, although some results have been mixed (Martin, Rao, & Sloan, 2009).…”
mentioning
confidence: 99%
“…Our data were collected from students at only one university, potentially limiting generalizability as values and education could vary across school or region. However, we do not feel that the students at the participating university differ signi cantly from students at other universities, and further, research has shown that cheating is a problem in Europe (Fox & Meijer, 2008;Orosz et al, 2016) and Asia (Koul, Clariana, Jitgarun, & Songsriwittaya, 2009;Tsui & Ngo, 2016) as well. Additionally, data were collected in a cross-sectional manner to help ensure con dentiality.…”
Section: Limitations and Future Researchmentioning
confidence: 72%